A case study of a transition to dialogic teaching as a process of gradual change. (October 2017) - Sedova, Klara
Abstract: The aim of this case study was to examine a process of gradual change in teaching practices during a development programme on dialogic teaching. The change process was seen to be non-linear. It included stages of regression – caused by a disharmony among the elements of dialogic teaching: indicators, principles and methods – and stages of progress which, on the contrary, came into effect when the partial elements were successfully brought into a harmonious relationship. The reflective interviews played a key role in the process of change, providing a tool for recognising disharmony and for creating a plan to overcome it. Highlights: We examine the process of a gradual transformation of teaching practices. The process of change is non-linear and includes stages of acceleration and regression. Reflective interviews play an important role in the process of change. Reflective interviews enable appropriation of new pedagogical tools.